Pyrochlore structure Bi2Ti2O7 doped magnesium hydride hydrogen storage material and preparation method thereof

By doping the pyrochlore structure Bi2Ti2O7 in the hydrogen storage material magnesium hydride, using hydrothermal reaction and ball milling technology, the existing catalyst preparation process is complicated and the catalytic efficiency is low, and the hydrogen absorption and release performance and kinetic performance of MgH2 are significantly improved. .

CN119390010APending Publication Date: 2025-02-07XIAN TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411316813.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, magnesium hydride (MgH2) of hydrogen storage material has high thermal stability and slow hydrogen absorption and release kinetic properties, resulting in limited development in practical applications. The existing catalysts have problems such as cumbersome preparation process, single structure and low catalytic efficiency.

Method used

A hydrogen storage material with magnesium hydride doped with magnesium hydride is adopted using a cocoaluminite structure, and the Bi2Ti2O7 catalyst is uniformly mixed with MgH2 through the preparation method of Bi2Ti2O7, including hydrothermal reaction and ball milling technology, to form a composite material.

Benefits of technology

It improves the hydrogen absorption and release performance of MgH2, reduces the initial hydrogen release temperature, increases the hydrogen release amount, significantly improves the kinetic performance of hydrogen storage materials, and is simple in the preparation process and low in energy consumption, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390010A_ABST
    Figure CN119390010A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen storage materials, in particular to a pyrochlore structure Bi2Ti2O7 doped magnesium hydride hydrogen storage material and a preparation method thereof. Comprising the following steps: firstly, adding bismuth nitrate pentahydrate into an acetone solution, and uniformly stirring; dropwise adding tetrabutyl titanate into the mixture, and continuously stirring until the tetrabutyl titanate is completely dissolved; performing ultrasonic treatment on the solution, performing hydrothermal reaction, washing, performing suction filtration to obtain sediment, and drying; then calcining for a period of time in an air atmosphere to obtain Bi2Ti2O7; and finally, grinding the MgH2 and 8 to 12 weight percent of Bi2Ti2O7 catalyst together in an inert atmosphere, so as to obtain the hydrogen storage material with the Bi2Ti2O7 doped with the magnesium hydride. The preparation process is simple, the Bi2Ti2O7 microspheres are synthesized by adopting a surfactant-free and template-free liquid phase method, the energy consumption is low, and the pollution is small; the hollow spherical catalyst can greatly enhance the ball milling effect, is beneficial to uniform distribution on an MgH2 matrix, and reduces hydrogen storage capacity recession; the Bi2Ti2O7 doped magnesium hydride hydrogen storage material synthesized by the method disclosed by the invention has the hydrogen desorption initial temperature of 187 DEG C and the hydrogen desorption amount of 6.8 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen storage materials, and in particular to a method for preparing a pyrochlore structure Bi2Ti2O7 doped magnesium hydride hydrogen storage material. Background Art

[0002] At present, among solid hydrogen storage materials, magnesium hydride (MgH2) has the advantages of high safety, low price, good cycle reversibility and high hydrogen storage capacity (7.6wt%), and is a hydrogen storage material with great application potential. However, high thermal stability and slow hydrogen absorption and desorption kinetics have always restricted the development of MgH2 in practical applications. In order to solve the above problems, it can be improved by adding catalyst modification, component substitution modification, surface treatment modification, nano-sizing and other methods. Among these strategies, adding catalysts can accelerate the hydrogen transfer process and significantly improve the kinetic properties of hydrogen storage materials. Among them, metal oxides have significant advantages. They can be adsorbed on the surface of MgH2 or form a new phase with MgH2 at the same time. In addition, metal oxides are highly brittle and are easier to disperse into the MgH2 system using ball milling technology, thereby reducing their grain size and activation energy. It is an important catalyst to improve the hydrogen storage performance of MgH2. However, in the prior art, many catalysts have problems such as cumbersome preparation process, simple crystal structure, slow catalytic process, and insufficient catalytic efficiency. How to develop a catalyst with a special crystal structure and excellent catalytic effect is a problem we need to consider.

[0003] There are many methods for improving the hydrogen storage performance of MgH2 by catalyst doping that have been disclosed. For example, the document with application number "CN202211052454.4" discloses "a carbon-coated CoNi bimetallic hydrogen storage catalyst and its preparation method and application". Its technical solution is: a method for preparing a carbon-coated CoNi bimetallic hydrogen storage catalyst, including the preparation steps of CoNi bimetallic MOF materials and the preparation steps of carbon-coated CoNi bimetallic composite materials. However, the problems are that the structure is single, the production process is cumbersome, and it is not suitable for mass production; because the CoNi bimetallic MOF material is not an oxide and does not have strong brittleness, it cannot be completely dispersed into the MgH2 system using ball milling technology, resulting in uneven distribution on the MgH2 matrix; and because the MOF material composed of Co and Ni has a single structure, the initial hydrogen release temperature and the hydrogen release peak temperature are relatively high; because the two elements Co and Ni do not fully react with the Mg element in a reversible manner during the hydrogen release process of the catalyst catalyzing MgH2, the initial catalytic efficiency of the catalyst is not high enough. Summary of the invention

[0004] The purpose of the present invention is to provide a hydrogen storage material of Bi2Ti2O7 doped with magnesium hydride having a special crystal type, and a preparation method thereof, so as to solve the problems in the prior art of single compound structure, complicated production process, low catalytic efficiency and serious attenuation of hydrogen release with temperature compared with the initial hydrogen release of MgH2.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0006] A method for preparing a pyrochlore structure Bi2Ti2O7 doped with magnesium hydride hydrogen storage material comprises the following steps:

[0007] Step 1) Preparation of Bi2Ti2O7 precursor: Add a certain amount of bismuth nitrate pentahydrate into acetone solution and stir evenly; drop tetrabutyl titanate into the above mixture and continue stirring until it is completely dissolved;

[0008] Step 2) placing the solution in an ultrasonic machine for ultrasonication, then transferring the solution to an autoclave and placing it in an oven for hydrothermal reaction, naturally cooling to room temperature, collecting the hydrothermal sample sediment, washing with deionized water and anhydrous ethanol for several times, collecting the sediment after filtration, and then drying it by air;

[0009] Step 3) The dried powder is transferred to a muffle furnace and calcined in air for a period of time to obtain Bi2Ti2O 7;

[0010] Step 4) Grinding MgH2 and 8-12 wt% of Bi2Ti2O7 catalyst together by a planetary ball mill under Ar atmosphere to obtain Bi2Ti2O7 doped magnesium hydride hydrogen storage material.

[0011] Furthermore, in the above step 1, the amount of Bi(NO3)3·5H2O, acetone solution and tetrabutyl titanate is 1mmol:20ml:1mmol.

[0012] Furthermore, in the above step 1, the stirring time for both times is 100-120 min.

[0013] Furthermore, in the above step 2, the hydrothermal reaction is carried out at 100-120° C. for 12-15 hours.

[0014] Furthermore, in the above step 2, the mixture is first washed with deionized water and filtered for 3-5 times, then washed with anhydrous ethanol and filtered for 3-5 times, and dried at 60-80° C. for 4-6 hours.

[0015] Furthermore, in the above step 3, the calcination condition is calcination at 600° C. for 3-4 hours.

[0016] Furthermore, in the above step 4, the ball-to-material ratio is 60:1, the ball milling speed is 400-500 r / min, and the ball milling time is 8-10 h.

[0017] Furthermore, a pyrochlore structure Bi2Ti2O7 doped with magnesium hydride hydrogen storage material prepared by the above preparation method

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The oxide catalyst proposed in the present invention has a pyrochlore structure, and the general formula of the pyrochlore structure is A2B2O7, in which (BO6) octahedrons are connected along the three-dimensional space through common oxygen vertices to form a skeleton. The (BO6) octahedron has a slightly distorted appearance, and the A ion is located in the gap of the BO6 skeleton, with a special structure. Studies have shown that many elements in transition metal elements have a lot of single electrons in their electronic configuration, which are easy to lose and have variable valence states. Among them, the change in valence state of metal ions with higher valence states during the reaction can significantly promote the charge transfer between magnesium and hydrogen molecules, thereby promoting its catalytic effect. The Bi2Ti2O7 crystal structure proposed in the present invention is unique, composed of Bi and Ti elements, and presents a special crystal arrangement. Among transition metals, Ti and its derivatives have always been at the forefront of applied research as catalysts for improving the hydrogen storage performance of MgH2. Due to the multivalence and high catalytic activity of Ti, active Ti-containing substances have a positive effect on the hydrogen absorption and release behavior of MgH2. However, as a transition metal element, the catalytic effect of Bi is often ignored by researchers. Bi can play a role in adjusting the valence state of the Ti element in metal oxides. Therefore, the present invention uses Bi and Ti as main components to study and prepare a new type of pyrochlore structure oxide catalyst. The crystal structure of Bi2Ti2O7 belongs to the structure of oxide minerals and has a cubic crystal system. In the crystal structure, Bi and Ti elements are interconnected with oxygen atoms as bridges to form a complex lattice structure. According to research, this special lattice structure enables it to have excellent catalytic performance; the Bi2Ti2O7 prepared by the present invention has a hollow spherical structure, which enables it to have a higher specific surface area and a thinner shell, which helps the oxide to be fully mixed with MgH2 during the ball milling process, and the hollow spherical structure has a clearer active site, which is beneficial to improve the catalytic efficiency, reduce the initial hydrogen release temperature, and improve the hydrogen release kinetics. Through experimental analysis, we determined that the combination of Bi and Ti elements under a special chemical reaction can make it have an excellent catalytic effect on MgH2.

[0020] 2. The preparation process of the present invention is simple. The liquid phase method without surfactant and template is used to synthesize Bi2Ti2O7 microspheres, which has low energy consumption and little pollution. The raw materials are cheap and low-cost. In the preparation process, bismuth nitrate pentahydrate and tetrabutyl titanate are used as the main raw materials, and acetone is used as the solvent for hydrothermal reaction. Acetone is relatively stable to the oxidant and will not be oxidized by nitric acid at room temperature, so that its special crystal structure can be formed. After the hydrothermal reaction is completed, the precursor is placed in a muffle furnace and calcined in an air atmosphere by calcination technology to obtain a Bi2Ti2O7 high-valent bimetallic oxide with a microscopic morphology of agglomerated hollow flower ball-shaped pyrochlore structure. The hollow spherical Bi2Ti2O7 itself has the characteristics of stable properties and structure and is not easy to collapse; the agglomerated spherical particles effectively expose the oxide surface with abundant defects and pores, providing more catalytic active sites, thereby increasing the catalytic efficiency of the catalyst; the ball milling effect can be greatly enhanced, which is conducive to the uniform distribution on the MgH2 matrix.

[0021] 3. The present invention dopes the prepared spherical Bi2Ti2O7 catalyst into MgH2 by grinding, uses stainless steel beads in the grinding, and ball mills the raw materials at a ball-to-material ratio of 60:1. The in-situ generated Bi2Mg2 and Ti have a synergistic effect, which can effectively improve the hydrogen absorption and desorption performance of MgH2. The initial dehydrogenation temperature of the Bi2Ti2O7 doped magnesium hydride hydrogen storage material synthesized by the method of the present invention is 187°C, and the dehydrogenation amount reaches 6.8wt%. Compared with the prior art, it has better hydrogen storage performance and activation energy, and has broad application prospects in the field of hydrogen storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD pattern of the Bi2Ti2O7 catalyst material prepared in Example 1;

[0023] Figure 2 This is the XPS spectrum of the Bi2Ti2O7 catalyst material prepared in Example 1;

[0024] Figure 3 This is a scanning electron microscope image of the Bi2Ti2O7 catalyst material prepared in Example 1;

[0025] Figure 4 This is a transmission electron microscope image of the Bi2Ti2O7-MgH2 composite material prepared in Example 1;

[0026] Figure 5 The TPD curves of the Bi2Ti2O7-MgH2 composite materials with different doping amounts prepared in Example 1;

[0027] Figure 6 This is a test diagram of the isothermal hydrogen desorption performance of the Bi2Ti2O7-MgH2 composite material prepared in Example 1 at different temperatures;

[0028] Figure 7 TPD curves prepared in Example 1 with different catalysts added;

[0029] Figure 8 This is a test diagram of isothermal hydrogen release performance at different temperatures of MgH2 prepared in Example 1;

[0030] Fig. 9 DSC curves and Kissinger curves of the Bi2Ti2O7-MgH2 composite material prepared in Example 1 at different heating rates;

[0031] Fig.10 DSC curves and Kissinger curves of ball-milled MgH2 without catalyst prepared in Example 1 at different heating rates;

[0032] Fig.11 XRD patterns of the Bi2Ti2O7-MgH2 composite material prepared in Example 1 after ball milling, dehydrogenation and hydrogen absorption;

[0033] Fig.12 The XPS spectra of Bi2Ti2O7 and MgH2 prepared in Example 1 before and after ball milling are compared;

[0034] Fig.13 The XPS spectra of the element Bi of the Bi2Ti2O7-MgH2 composite material prepared in Example 1 after ball milling, dehydrogenation and hydrogen absorption are compared;

[0035] Fig.14 This is a bar chart of the hydrogen desorption cycle life of the Bi2Ti2O7-MgH2 composite material prepared in Example 1.

[0036] Fig.15 These are scanning electron microscope comparison images of the Bi2Ti2O7-MgH2 composite material prepared in Example 1 after ball milling, after dehydrogenation, and after ten cycles of dehydrogenation. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below through embodiments and drawings.

[0038] Embodiment 1, a method for preparing a hydrogen storage material of pyrochlore structure Bi2Ti2O7 doped with magnesium hydride, comprising the following steps:

[0039] Step 1, preparation of Bi2Ti2O7 precursor: 0.548 g of bismuth nitrate pentahydrate was added to 20 ml of acetone solution to form solution A, and then 0.34 g of tetrabutyl titanate was dropped into solution A using a rubber-tipped dropper, and solution B was obtained after vigorous stirring for 2 h;

[0040] Step 2, preparation of precursor Bi2Ti2O7: firstly, solution B is placed in an ultrasonic machine for 15 minutes; then, solution B is subjected to a solvothermal reaction at a reaction temperature of 120°C and a reaction time of 12 hours. After the reaction is completed, the reactants are washed with deionized water and anhydrous ethanol respectively using the two washing liquids for three times; finally, air drying is performed at a drying temperature of 60°C and a drying time of 6 hours to obtain the precursor Bi2Ti2O7;

[0041] Step 3, preparation of pyrochlore structure Bi2Ti2O7: calcining the precursor obtained in step 1 under air conditions at a calcination temperature of 600°C and a calcination time of 3 hours to obtain pyrochlore structure Bi2Ti2O7.

[0042] In order to prove the composition of Bi2Ti2O7, XRD test was carried out. The test results are as follows Figure 1 As shown, the diffraction peak of the prepared material is in good agreement with the standard peak crystal plane of Bi2Ti2O7. The test results show that the composition of Bi2Ti2O7 is Bi2Ti2O7, and it has high purity and high crystallinity.

[0043] In addition, the XPS spectrum of Bi2Ti2O7 was tested to further prove that the synthesized sample was pure Bi2Ti2O7 particles. Figure 2 This is the XPS spectrum of Bi2Ti2O7. The binding energy peak of 158.81 eV is attributed to Bi 4f 7 / 2 , the binding energy peak of 164.11 eV is attributed to Bi 4f 5 / 2 , reflecting the Bi in the Bi2Ti2O7 octahedron 3+ In addition, Ti 2p 3 / 2 The peak value is at 457.6eV, Ti2p 1 / 2 The peak value is located at 463.6eV. These results show that the main chemical states of Ti on the sample surface are Ti(IV), Ti 2p 1 / 2 and Bi4d 3 / 2 There is a broad peak near 465.0 eV. These conclusions prove the successful synthesis of Bi2Ti2O7.

[0044] In order to verify the microstructure of Bi2Ti2O7 obtained in step 2, SEM test was performed. The test results are as follows Figure 3 As shown, the microstructure obtained through SEM testing is agglomerated hollow flower balls.

[0045] Step 4, preparation of hydrogen storage materials: under argon conditions, with Bi2Ti2O7 added in an amount of 10wt% of the total mass, Bi2Ti2O7 is mixed with MgH2, and high-energy ball milling is performed at a ball-to-material ratio of 60:1, a ball milling speed of 400rpm, and a total ball milling time of 6h, wherein the high-energy ball milling method is forward and reverse ball milling, the single ball milling time is 12min, and the ball milling interval is 6min, to obtain a MgH2-based hydrogen storage material named MgH2-10Bi2Ti2O7.

[0046] Figure 4 The figure shows the transmission electron microscope image of the prepared Bi2Ti2O7-MgH2 composite material. The black material dispersed inside may be the magnesium-bismuth alloy formed during the reaction. The hollow structure at the edge is observed, which further clarifies that Bi2Ti2O7 is a hollow spherical structure and the hollow structure still exists after the ball milling reaction. The hollow spherical Bi2Ti2O7 is fully mixed with MgH2, providing active sites to promote the hydrogen absorption and desorption reaction. By observing the interplanar spacing of Bi2Ti2O7-MgH2, it can be found that d=0.251 is the (101 crystal plane) of MgH2, while the surrounding d=0.236 and d=0.298 are the (662) and (444) crystal planes of Bi2Ti2O7, respectively. It is judged that after the ball milling and mixing of Bi2Ti2O7 and MgH2, the in-situ coating promotes the catalytic effect of the oxide and improves its hydrogen storage performance.

[0047] The preparation of Example 2 and Example 3 is the same as that of Example 1, except that the doping amount of Bi2Ti2O7 is adjusted to 8wt% and 10wt%.

[0048] Comparative Example 1 is MgH2.

[0049] In order to prove the effect of Bi2Ti2O7 and its doping amount on the dehydrogenation performance in Bi2Ti2O7-based magnesium hydride hydrogen storage materials, a heating rate of 5°C / min and a dehydrogenation temperature of 450°C were used to perform a dehydrogenation test. Figure 5 As shown in Table 1, when the doping amount of the catalyst is 10wt%, its initial dehydrogenation temperature is 187°C and the dehydrogenation amount is 6.82wt%. Combined with the test results of the subsequent comparative examples, it can be seen that when the doping amount of Bi2Ti2O7 is 10wt%, it has the best dehydrogenation performance, and Example 1 is the best example.

[0050] Table 1 Summary of initial dehydrogenation temperature and dehydrogenation amount at different doping levels

[0051] Comparative Example 1 Example 1 Example 2 Example 3 Catalyst doping amount / wt% 0 10 8 12 Initial hydrogen release temperature / ℃ 335 187 202 220 Hydrogen release / wt% 7.4 6.82 6.55 6.64

[0052] The specific test method of isothermal hydrogen desorption test is: the furnace body is rapidly heated to a specified temperature for isothermal hydrogen desorption test. When complete hydrogen desorption is achieved, the target hydrogen desorption temperatures are 290°C, 270°C, and 250°C, respectively. The MgH2-10Bi2Ti2O7 of Example 1 is selected for testing, and the test results are as follows: Figure 6 As shown in Table 2, it can be seen that when the temperature rises to 290°C, the hydrogen release amount of the sample can reach 6.37wt%. Figure 7 As shown, MgH2 has not yet reached the temperature at which hydrogen release begins, which proves that the addition of catalyst Bi2Ti2O7 significantly improves the performance of MgH2.

[0053] Table 2 Summary of isothermal hydrogen desorption at different target desorption temperatures

[0054] Isothermal dehydrogenation temperature / ℃ 250℃ 270℃ 290℃ Hydrogen release within 15min / wt% 3.6 5.3 6.37

[0055] In order to prove the role of Bi and Ti content in the technical solution, that is, the role of the preparation method of the present invention, comparative examples 2 and 3 are provided, and the oxides of Bi and Ti with different contents are respectively prepared as raw materials by the control variable method to prepare magnesium hydride hydrogen storage materials; for comparison with Example 1, the doping amount is 10wt%. At the same time, comparative example 1 is provided, and the magnesium hydride hydrogen storage material with a doping amount of 0wt% is used as a reference experiment.

[0056] Comparative Example 2:

[0057] A method for preparing a magnesium hydride hydrogen storage material based on an oxide in which Bi:Ti=1:2 in a catalyst, wherein the steps not specifically described are the same as those in Example 1, except that in step 1, 1 mmol of bismuth nitrate pentahydrate and 2 mmol of tetrabutyl titanate are added to acetone for hydrothermal reaction to obtain BiTiO-1, and then step 3 is performed; and in step 3, BiTiO-1 is used instead of Bi2Ti2O7, i.e., 0.03 g of BiTiO-1 and 0.27 g of magnesium hydride are weighed and ball-milled, and the obtained material is named MgH2-10BiTiO-1.

[0058] The results of the temperature rise hydrogen release test of MgH2-10BiTiO-1 are as follows Figure 8 As shown, the material starts to release hydrogen at 205°C, and the final amount of hydrogen released is 6.62wt%. Compared with the test results of Comparative Example 1, it can be seen that the introduction of Bi and Ti reduces the dehydrogenation temperature of MgH2 from 335°C to 205°C, but compared with the test results of Example 1, it can be seen that the introduction of more Ti actually reduces the performance of the catalyst. The reason for this is that the increase in tetrabutyl titanate increases the content of Ti, thereby changing the crystal structure of the oxide, resulting in a decrease in hydrogen storage performance.

[0059] Comparative Example 3

[0060] A method for preparing a magnesium hydride hydrogen storage material based on an oxide in which Bi:Ti=1:3 in a catalyst, wherein the steps not specifically described are the same as those in Example 1, except that in the step 1, 1 mmol of bismuth nitrate pentahydrate and 3 mmol of tetrabutyl titanate are added to acetone for hydrothermal reaction to obtain BiTiO-2, and then step 3 is performed; and in the step 3, BiTiO-2 is used instead of Bi2Ti2O7, i.e., 0.03 g of BiTiO-2 and 0.27 g of magnesium hydride are weighed and ball-milled, and the obtained material is named MgH2-10BiTiO-2.

[0061] The results of the temperature rise hydrogen release test of MgH2-10BiTiO-2 are as follows: Figure 8 As shown, the material starts to release hydrogen at 231°C, and the final amount of hydrogen released is 6.44wt%. Compared with the test results of Comparative Example 1, it can be seen that the introduction of Bi and Ti reduces the dehydrogenation temperature of MgH2 from 335°C to 231°C, but compared with the test results of Example 1 and Comparative Example 2, it can be seen that the further increase of Ti causes the catalyst performance to decrease again, confirming the influence of the crystal structure of the oxide on the hydrogen storage performance.

[0062] The isothermal hydrogen test of MgH2 in Comparative Example 1 is as follows Figure 7 As shown, at 360°C, only 1.36 wt% of hydrogen is released within 15 minutes.

[0063] Comparison of the test results with those of Example 1 shows that the introduction of Bi2Ti2O7 not only significantly reduces the dehydrogenation temperature to 187°C, but also significantly increases the isothermal dehydrogenation amount.

[0064] By comparing the test results of Example 1 with those of Comparative Examples 1, 2 and 3, it can be seen that the introduction of Bi2Ti2O7 with a pyrochlore structure can not only significantly reduce the initial hydrogen desorption temperature of MgH2, but also significantly increase the amount of hydrogen desorption, that is, significantly improve the dehydrogenation kinetics. In addition, by comparing with Comparative Examples 2 and 3, it can be seen that the BiTiO compound prepared based on Bi2Ti2O7 has better kinetics than other structures, that is, Bi and Ti are combined to form a special crystal structure to produce a synergistic effect, which further improves the catalytic effect of MgH2.

[0065] Fig. 9 DSC curves and Kissinger curves of the Bi2Ti2O7-MgH2 composite material prepared in Example 1 at different heating rates; Fig.10 The DSC curves and Kissinger curves of ball-milled MgH2 without catalyst at different heating rates show that the activation energy of the composite material is reduced to 82.14 KJ mol -1 .

[0066] Fig.11 The XRD patterns of the ball-milled state (Ball-milled), hydrogen-absorbed state (1st DEH), and re-hydrogen-absorbed state (1st-REH) of the Bi2Ti2O7-MgH2 composite material prepared in Example 1. Fig.10 It can be seen that the spectrum after dehydrogenation is mainly composed of Mg and Bi2Mg2, and a faint Ti phase is also detected. It can be seen that the dehydrogenation of MgH2 is relatively complete, and a new phase Bi2Mg2 is formed. After hydrogen absorption, a large amount of MgH2 phase and a small amount of Mg phase and TiO2 phase are detected. It can be seen that the hydrogen absorption is not complete, which is also the main reason for the reduction in hydrogen release after the cycle.

[0067] Fig.12 The XPS spectra of Bi2Ti2O7 and Bi2Ti2O7-MgH2 composite materials prepared in Example 1 are compared. After ball milling, the 4f 5 / 2 Spin-orbit and Bi 4f 7 / 2 The spin orbit shifted to low energy and a new diffraction peak appeared. After analysis, we found that it was because part of Bi2O3 was reduced to Bi element. A small amount of catalyst was reduced during the ball milling process, and the valence state of part of the Bi element was reduced from +3 to 0. It was observed that the binding energy of Ti shifted slightly to low energy, and the valence state did not change significantly. 4+ It can be concluded that Bi2Ti2O7 is reduced in the chemical reaction with magnesium hydride during ball milling, and the in-situ generated metal particles can effectively improve the kinetic properties of MgH2.

[0068] Fig.13 The XPS spectra of the Bi element after ball milling and hydrogen absorption and desorption of the Bi2Ti2O7-MgH2 composite material prepared in Example 1 are compared. In order to further confirm the specific process of the reaction, we tested the XPS diffraction spectra of the ball milling product, hydrogen desorption product and hydrogen absorption product of the MgH2-10wt% Bi2Ti2O7 sample respectively, and confirmed the existence form of the Bi element in different cycle stages through XPS analysis.

[0069] Fig.13 The XPS spectra of the three samples on the Bi 4f orbital are shown in Figure 2. After ball milling, the Bi 4fXPS spectra of the ball milled product are decomposed into 4f 5 / 2 and 4f 7 / 2 Spin double orbit, two pairs of XPS peaks are obtained, which are Bi2O3 (162.34eV / 157.43eV) and Bi element (160.56eV / 155.24eV).

[0070] During the ball milling process, part of the Bi element has been reduced, and the valence state has changed from +2 to 0. During the dehydrogenation process, the catalyst continues to be reduced, and the diffraction peak intensity of Bi2O3 in the dehydrogenation product is significantly weakened, while the diffraction peak intensity of Bi is enhanced, indicating that during the dehydrogenation process, Bi reacts with Mg to form Bi2Mg2 alloy. In the Bi 4f XPS spectrum of the hydrogen absorption product, the position of the diffraction peak is basically the same as that of the dehydrogenation product, but the diffraction peak area of ​​Bi is slightly reduced, indicating that the redox reaction is partially reversible and the Bi element is oxidized to a high valence state.

[0071] The above test results indicate that during the ball milling and the first hydrogen absorption and desorption cycle, the Bi2Ti2O7 catalyst is reduced, wherein the Bi element is first reduced to a single substance of Bi, and further reacts with Mg during the first hydrogen desorption process to form a Bi2Mg2 alloy, which improves the hydrogen absorption and desorption performance of the system and leads to a decrease in the hydrogen storage capacity.

[0072] Fig.14 This is a bar chart of the hydrogen desorption cycle life of the Bi2Ti2O7-MgH2 composite material prepared in Example 1. The cycle retention rate reaches 72%, which is slightly attenuated compared with the initial hydrogen desorption. XPS spectrum analysis may be due to the formation of Bi2Mg2 alloy during the hydrogen absorption and desorption process and the agglomeration of particles during the reaction process.

[0073] Fig.15 The scanning electron microscope comparison images of the Bi2Ti2O7-MgH2 composite material after ball milling, dehydrogenation and ten cycles of dehydrogenation can also confirm the above conjecture. By observing the scanning electron microscope images, it was found that the particles agglomerated after absorbing hydrogen and the particles became larger, resulting in a decay in the amount of hydrogen desorption for the second time. After ten cycles of dehydrogenation, the particles were observed to be small and dispersed, which can also explain why the cyclic dehydrogenation tended to stabilize from the sixth time.

[0074] The above is an explanation of the specific implementation of the present invention, rather than a limitation of the present invention. Those skilled in the relevant technical field can also make various equivalent technical solutions without departing from the scope of the present invention, so all equivalent technical solutions should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrogen storage material of pyrochlore structure Bi2Ti2O7 doped with magnesium hydride, characterized in that: The following steps are involved: Step 1) Preparation of Bi2Ti2O7 precursor: Add a certain amount of bismuth nitrate pentahydrate into acetone solution and stir evenly; drop tetrabutyl titanate into the above mixture and continue stirring until it is completely dissolved; Step 2) placing the solution in an ultrasonic machine for ultrasonication, then transferring the solution to an autoclave and placing it in an oven for hydrothermal reaction, naturally cooling to room temperature, collecting the hydrothermal sample sediment, washing it with deionized water and anhydrous ethanol for several times, collecting the sediment after filtration, and then drying it in an air atmosphere; Step 3) The dried powder is transferred to a muffle furnace and calcined in an air atmosphere for a period of time to obtain Bi2Ti2O7 with a pyrochlore structure; Step 4) Grind MgH2 and 8-12 wt% Bi2Ti2O7 catalyst together by a planetary ball mill under Ar atmosphere to obtain Bi2Ti2O7 doped magnesium hydride hydrogen storage material.

2. The method for preparing a pyrochlore structure Bi2Ti2O7 doped magnesium hydride hydrogen storage material according to claim 1, characterized in that: In the step 1, the amount of bismuth nitrate pentahydrate, acetone solution and tetrabutyl titanate used is 1 mmol: 20 ml: 1 mmol.

3. The method for preparing a pyrochlore structure Bi2Ti2O7 doped magnesium hydride hydrogen storage material according to claim 2, characterized in that: In the step 1, the stirring time is 100-120 min for both times.

4. The method for preparing a pyrochlore structure Bi2Ti2O7 doped magnesium hydride hydrogen storage material according to claim 3, characterized in that: In step 2, the hydrothermal reaction is carried out at 100-120° C. for 12-15 hours.

5. The method for preparing a pyrochlore structure Bi2Ti2O7 doped magnesium hydride hydrogen storage material according to claim 4, characterized in that: In the step 2, the product is first washed and filtered with deionized water for 3-5 times, then washed and filtered with anhydrous ethanol for 3-5 times, and dried at 60-80° C. for 4-6 hours.

6. The method for preparing a pyrochlore structure Bi2Ti2O7 doped magnesium hydride hydrogen storage material according to claim 5, characterized in that: In the step 3, the calcination condition is calcination at 600° C. for 3-4 hours.

7. The method for preparing a pyrochlore structure Bi2Ti2O7 doped magnesium hydride hydrogen storage material according to claim 6, characterized in that: In the step 4, the ball-to-material ratio is 60:1, the ball milling speed is 400-500 r / min, and the ball milling time is 8-10 h.

8. A hydrogen storage material of pyrochlore structure Bi2Ti2O7 doped with magnesium hydride obtained by the preparation method according to claim 1.

Citation Information

Patent Citations

  • Carbon-coated CoNi bimetallic hydrogen storage catalyst as well as preparation method and application thereof

    CN115301240A